Tratamento Farmacológico da Síndrome das Pernas Inquietas Secundária: Revisão Sistemática - Oliveira, Márcio Moysés de [UNIFESP] (2009)
Introduction: Restless legs syndrome (RLS) is common and often misdiagnosed entity in the general population and it may be more common in dialysis patients, with an estimated prevalence of 6.6% to 21.5%. Objective: The treatment for uremic RLS has been controversial and therefore a systematic synthesis of the evidence is needed in order to evaluate the effectiveness and safety of treatments for uremic RLS. Method: This was a systematic review of randomized or quasirandomized double-blind trials on treatments for uremic RLS. The outcomes considered were relief of RLS symptoms marked on a validated scale, subjective sleep quality, sleep quality measured using night polysomnography and actigraphy, quality of life measured subjectively and adverse events associated with these treatments. Results: Six eligible clinical trials were included. The results from subjective analyses in these studies were divergent, although objective analyses in one trial showed that there was a statistically significant improvement in periodic leg movement (PLM) during time asleep (PLM) in the treatment group. No combined analysis (meta-analysis) was performed. The most common adverse event seen was gastrointestinal symptoms. Conclusion: Only a few therapeutic trials on uremic patients with RLS have been published, and there is not enough to give scientific evidence favoring any specific therapeutic regimen for uremic-associated RLS. Therapy with levodopa, dopaminergics agonists, anticonvulsants, and clonidine tend to be effective, but more studies are need. Key words: systematic review, restless legs syndrome, uremic, end-stage renal disease.